ASSA13-03-10 The Protein Expression of Mitochondrial Trx2 in Selenium Deficiency Rat Hearts and Its Effect on Mitochondria. (29th April 2013) - Ming, Zhang; Jin, Wei; Hu, Shan; Rui, Yan; Lin, Lin; Xiaoqing, Pan
Abstract : Objectives: To study the dynamic changes of thioredoxin 2 (Trx2) protein expression in the cardiac mitochondria of selenium deficiency rats and its effect on the cardiac mitochondria damage. Methods: Forty-eight rats were randomised into normal control group (n = 24) and selenium deficiency model group (n = 24). When rats were fed for 10 weeks, 20 weeks, 30 weeks and 40 weeks respectively, the cardiac function was determined by carotid artery intubation. At the corresponding time points, the damage of cardiac mitochondria was observed under electron microscopy, and the mitochondrial stereological parameters including surface density (Sv), volume density (Vv) and specific surface (Rsv, surface-to-volume ratio) were further studied. The cardiac mitochondria were extracted from the rats at the corresponding time points for assessing the enzyme activities of succinate dehydrogenase (SDH) and cytochrome c oxidase, and studying the protein expression of Trx2 using western-blot. Results: (1) Compared with the corresponding control group, the rats in the model group had notable decreased cardiac function, and the damage significantly aggravated with the time extension of low selenium ( P, and remarkable increase in Vv in the selenium deficiency rat hearts compared with the corresponding control group ( P mitochondrial stereological parameters and the enzyme activities in the model group were more notable with the time extension of low selenium ( PP Sv, Rsv, SDH and COX, and negative correlation with Vv ( P < 0.01). Conclusions: Selenium deficiency down-regulates the protein expression of mitochondrial Trx2 in the rat heart, which results in cardiac mitochondrial injury and the ultimate progress of heart failure.